Optical interferometric studies of a confined liquid free surface: meniscus-effect compensation and time evolution of the surface - Bourimborde, Lea V. (1996)
A fruitful approach to the studies of a liquid free surface is demonstrated. Using optical interferential techniques, the free surface of nonvolatile and volatile confined liquids is analyzed. Various wall con tainer types are investigated. Besides the classical plane wall, experiments are performed by using cylindrical and toroidal walls. In these last cases, the meniscus effect that affects the free surface of the liquid is compensated. Then, it is possible to obtain completely flat free surfaces of liquids up to 80% of their total. Interferometric experiments are also described to measure the inclination of the site with respect to the local horizon, represented by the liquid flat free surface, and to follow the temporal evolution of such free surfaces affected by different conditions.